The financial burden of acute odontogenic infections: the South Australian experience. (13th November 2019) - Han, J; Liau, I; Bayetto, K; May, B; Goss, A; Sambrook, P; Cheng, A
Abstract: Background: Acute odontogenic infections are a common surgical emergency managed by public hospitals in Australia which cause considerable patient morbidity and occasionally, mortality. Despite posing a significant public health burden, Australian data evaluating the cost of the management of these patients are lacking. This study assessed the patient and treatment variables associated with inpatient management of deep odontogenic infections, and their respective financial impact, at a statewide Oral & Maxillofacial service. Methods: A retrospective audit was carried out of patients with deep odontogenic infections at our institution, over a 7‐year period. The primary outcome was the total cost of admission. Secondary outcomes included treatment received, operating room time, return‐to‐theatre, length of admission (LOS), and intensive care unit (ICU) use. Cost variables were assessed against the total LOS and ICU use to determine clinical predictors affecting outcome. Results: Four hundred and sixty two patients met the inclusion criteria. The average cost per patient was $12 228 Australian Dollars. After multivariate analysis, variables most significantly associated with increased cost of care and LOS were high‐risk infections with airway compromise, high admission white cell count and age. Conclusion: Hospital‐based management of deep‐space odontogenic infections engender significant costs compared to early primary care intervention such as a dental extraction ($181/extraction).